Advanced parallel architectures for 5G all-digital transmitters - Dinis, Daniel António da Costa (2019)
The fifth generation of mobile communications (5G) is being prepared and should be rolled out in the early coming years. Massive number of Radio-Frequency (RF) front-ends, peak data rates of 10 Gbps (everywhere and everytime), latencies lower than 10 msec and huge device densities are some of the expected disruptive capabilities. At the same time, previous generations can not be jeopardized, fostering the design of novel flexible and highly integrated radio transceivers able to support the simultaneous transmission of multi-band and multi-standard signals. The concept of all-digital transmission is being pointed out as a promising architecture to cope with such challenging requirements, due to its fully digital radio datapath. This thesis is focused on the proposal and validation of fully integrated and advanced digital transmitter architectures that excel the state-of-the-art in different figures of merit, such as transmission bandwidth, spectral purity, carrier agility, flexibility, and multi-band capability. The first part of this thesis introduces the concept of all-digital RF transmission. In particular, the foundations inherent to this thematic line are given, together with the recent advances reported in the state-of-the-art architectures.The core of this thesis, containing the main developments achieved during the Ph.D. work, is then presented and discussed. The first key contribution to the state-of-the-art is the use of cascaded Delta-Sigma (∆Σ) architectures to relax the analog filtering requirements of the conventional All-Digital Transmitters while maintaining the constant envelope waveform. Then, it is presented the first reported architecture where Antenna Arrays are directly driven by single-chip and single-bit All-Digital Transmitters, with promising results in terms of simplification of the RF front-ends and overall flexibility. Subsequently, the thesis proposes the first reported RF-stage All-Digital Transmitter that can be embedded within a single Field-Programmable Gate Array (FPGA) device. Thereupon, novel techniques to enable the design of wideband All-Digital Transmitters are reported. Finally, the design of concurrent multi-band transmitters is introduced. In particular, the design of agile and flexible dual and triple bands All-DigitalTransmitter (ADT) is demonstrated, which is a very important topic for scenarios that demand carrier aggregation. This Ph.D. contributes withseveral advances to the state-of-the-art of RF all-digital transmitters.